Pemanfaatan AI dalam Pendidikan: Meningkatkan Kualitas Pembelajaran di Kelas Digital - khudin, ahmad mifta (Maliki Interdisciplinary Journal, 2025)
In today's digital age, the use of information and communication technology has become increasingly crucial, especially in the field of education. In the era of digital education, the presence of artificial intelligence (AI) is seen as an innovative step that has the potential to improve the quality of learning in the classroom. This article explores various aspects of the utilization of artificial intelligence in education, such as benefits, challenges, and its implementation in learning settings. With a systematic and organized approach, this article aims to provide in-depth insights into how the integration of AI can create a better learning. The application of AI in education also poses complex challenges, including data privacy issues, dependence on technology, infrastructure limitations, and the need for specialized training for educators. Therefore, it is important to adopt a balanced approach to the use of AI in the digital classroom, ensuring that the technology supports education without compromising the fundamental values ​​of learning.